Exploring disparities in the diffusion and adoption of climate-smart agricultural and climate information system technologies in Senegal - Worou, Omonlola Nadine; Moore, Maya; Basse, Blaise Waly; Yessoufou, Adjani Nourou-Dine; Sarr, Etienne Aliouse; Gondwe, Therese Mwatitha; Joseph, Jacob Emanuel; Akinseye, Florounsho M.; Mbow, Khalifa (Frontiers in Environmental Economics, 2025)
Gender mainstreaming in the dissemination and adoption of climate-smart agricultural technologies (CSA) and access to the climate information services (CIS) can help mitigate the effects of climate change and reduce specific disadvantages suffered by women and young people. In this study, we are addressing gender and age-related disparities in CSA and climate information services (CIS). Focusing on 473 households in the Thies, Louga and Kaffrine regions of Senegal, the results of the average treatment effect (ATE) method reveal a higher rate of resilient seed adoption among women. However, the rate of adoption of micro-dosing techniques and the use of climate information are higher among youth. A negative and significant adoption gap (GAP) confirms that not all of the population had been exposed to CSA and CIS technologies, hence the existence of a non-exposure bias justifying further dissemination. These results indicate that future initiatives should focus not only on broadening their reach but also on customizing delivery approaches to address gender and age disparities in adoption capacity. Such targeted efforts would enhance the overall impact of CSA and CIS programs while fostering more equitable and inclusive climate adaptation pathways in Senegal.JEL ClassificationO33, Q12, J16.